2018
DOI: 10.1128/iai.00647-17
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Cyclic Di-GMP in Klebsiella pneumoniae Attenuate Virulence in the Lung

Abstract: The bacterial second messenger bis-(3'-5')-cyclic dimeric GMP (c-di-GMP) has been shown to influence the expression of virulence factors in certain pathogenic bacteria, but little is known about its activity in the increasingly antibiotic-resistant pathogen Here, the expression in of a heterologous diguanylate cyclase increased the bacterial c-di-GMP concentration and attenuated pathogenesis in murine pneumonia. This attenuation remained evident in mice lacking the c-di-GMP sensor STING, indicating that the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…This has been corroborated in murine models of K. pneumoniae infection with levels of c-di-GMP influencing the extent of pathology. Elevated c-di-GMP levels are associated with attenuated lung pathology and inflammation but increased fimbrial production [67]. Increased expression of fimbriae has been observed in the organisms that express the extended-spectrum β- lactamase (ESBL) [68] likely contributing to their ability to cause infection.…”
Section: K Pneumoniae Surface Structures Important In Pathogenesis: mentioning
confidence: 99%
See 1 more Smart Citation
“…This has been corroborated in murine models of K. pneumoniae infection with levels of c-di-GMP influencing the extent of pathology. Elevated c-di-GMP levels are associated with attenuated lung pathology and inflammation but increased fimbrial production [67]. Increased expression of fimbriae has been observed in the organisms that express the extended-spectrum β- lactamase (ESBL) [68] likely contributing to their ability to cause infection.…”
Section: K Pneumoniae Surface Structures Important In Pathogenesis: mentioning
confidence: 99%
“…A downstream regulator of type 3 fimbrial expression, MrkJ, is a phosphodiesterase that reduces c-di-GMP levels to suppress fimbrial expression and subsequent biofilm formation [77]. Modulation of the c-di-GMP system could possibly enhance clearance in the chronically colonized host [78] but could also lead to increased inflammation leading to worse clinical outcomes [67]. …”
Section: K Pneumoniae Surface Structures Important In Pathogenesis: mentioning
confidence: 99%
“…Another study has shown that c-di-GMP can be complexed with simple cell-penetrating peptides that enhance cellular delivery and biological activity in murine splenocytes but also that the bacterial 3′−3′-cGAMP is a superior stimulator of IFN genes ligand than c-di-GMP in human peripheral blood mononuclear cells (Yildiz et al, 2015). A more recent study has shown that expression of an inducible c-di-GMP-producing diguanylate cyclase in Klebsiella pneumonia increased endogenous concentrations of c-di-GMP which attenuated its virulence in the lung of mice (Rosen et al, 2017). Importantly, the attenuation of virulence was independent of STING, supporting the idea that CDNs can be used to influence pathogen virulence (Karaolis et al, 2007a,b; Rosen et al, 2017).…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%
“…A more recent study has shown that expression of an inducible c-di-GMP-producing diguanylate cyclase in Klebsiella pneumonia increased endogenous concentrations of c-di-GMP which attenuated its virulence in the lung of mice (Rosen et al, 2017). Importantly, the attenuation of virulence was independent of STING, supporting the idea that CDNs can be used to influence pathogen virulence (Karaolis et al, 2007a,b; Rosen et al, 2017). Indeed, the use of CDNs as adjuvants has increased in the last few years and will likely continue to expand as more pathogens and diseases are studied under this framework (Dubensky et al, 2013; Junkins et al, 2018; Karaolis et al, 2007a; Miyabe et al, 2014; Škrnjug et al, 2014).…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%
See 1 more Smart Citation